Screening Strongyloides spp. Infection from Wild Rodents Implications for Public Awareness and Attitudes on Zoonotic Diseases in Malang City, Indonesia - Kusumarini, Shelly; Danuarta, Muhammad Fernanda; Karami, Farhan; Yesica, Reza; Wisesa, Ida Bagus Gde Rama; Yudhana, Aditya; Nurhidayah, Nanis (Universitas Airlangga, 2022)
Strongyloidiasis is a nematode parasite with broader distribution proved to infect humans and animals. Strongyloides ratti common endoparasites infected rodent as the most adaptive population in various environments. We have currently raised concerning the neglected tropical diseases (NTDs) situations in Indonesia. This study aimed to understand the incidence of Strongyloides spp. infecting wild rodents in Malang City during October to December 2021 by stratified random sampling. A total of 50 rats (Rattus norvegicus, Rattus rattus diardii, Mus musculus), 26 male (52%) and 24 female (48%). Following 12 juveniles (24%) and 38 adults (76%). Coprology examinations use floatation and sedimentation methods immediately after the gastrointestinal tract's stool collection (GITs). We also administered a limited survey to get responses from 80 people (housewives, sellers, employee, and students) to obtain risk transmission, public awareness, and attitudes. We were continually analyzed data using the chi-squared and Fisher Exact Test. The microscopic examination of stools was 28% positively detected S. ratti. Our study found an association presented between the age of rats and Strongyloidiasis infections (p<0.05). However, the gender of rats did not have a significant association (p>0.05) to the S. ratti several infections. In addition, most participants did not understand the zoonotic disease and these infections, indicating a low-level knowledge 71 (88%), because better education supports the increase of awareness. However, almost all participants have good practice of hygiene and sanitation toward COVID-19 situations 72 (90%). The further study recommends investigating Strongyloidiasis infections in another species and increasing the education program for housewives and sellers in a traditional marketplace to have better knowledge.